A proposed teaching module for multiplying and factoring polynomials through physical models - Albana, Federico T. (Quezon City [s.n.], 1974)
The study presented a teaching module for multiplying and factoring polynomials through physical models. It also offered an alternative solution to the problem of solving polynomial equations.
Thesis (M.A.T.)--University of the Philippines.
Keywords: Polynomials; Algebra -- Programmed instruction; Algebra -- Study and teaching